Dietary characteristics associated with the risk of non‐alcoholic fatty liver disease and metabolic dysfunction‐associated steatotic liver disease in non‐obese Japanese participants: A cross‐sectional study - Hirokazu Taniguchi; Miho Ueda; Fumika Sano; Yukiko Kobayashi; Takatomo Shima (JGH Open)
Abstract Background and Aim Dietary characteristics associated with non‐alcoholic fatty liver disease (NAFLD) and metabolic dysfunction‐associated steatotic liver disease (MASLD) in non‐obese patients remain to be elucidated. This study examined the association of NAFLD and MASLD with dietary characteristics according to obesity status. Methods We performed a cross‐sectional study of 15 135 participants (n = 7568 men and 7567 women) aged 35–74 years using data of annual health checks between 2008 and 2020. Obesity was defined as BMI ≥ 25 kg/m2. Diagnosis of fatty liver was based on abdominal ultrasonography. Fatty‐liver‐related dietary characteristics were assessed using a self‐administered questionnaire. Results For non‐obese participants, NAFLD was found in 31.0% of men and 19.4% of women. Non‐obese MASLD was found in 27.6% of men and 18.1% of women. Multivariable‐adjusted stepwise logistic regression analysis indicated that, in males, both non‐obese NAFLD and non‐obese MASLD were significantly and negatively associated with “often eat sesame/nuts”, and positively associated with “often eat noodles/rice bowl” and “often eat evening meal” (P < 0.05). For non‐obese women, both NAFLD and MASLD were significantly and positively associated with “often eat sweet buns/bread with fillings” (P < 0.05). Adjusted analyses showed that all dietary characteristics were not significantly associated with the risk of NAFLD/MASLD in obese men and women. Conclusion This cross‐sectional study indicates the existence of sex and obesity differences in the association of NAFLD and MASLD with dietary characteristics. Our findings suggest that some dietary characteristics are associated with NAFLD and MASLD prevalence in non‐obese Japanese participants.